Cultural implications in the cranial morphology of peruvian precolumbian ethnic groups - Galvez Calla, Luis Hernando (2014)
The objective of the study was to relate the causative agent of cranial deformations with the cultural area, the suture closure and cranial forms, in the context of the craniofacial growth of pre-columbian peruvian population, included in the typological classification of Weiss. Sample: eighteen skulls representing pre-columbian ethnic groups of ancient Peru comprised within the typological classification of Weiss were selected from the curatorship human remains of National Museum of Archaeology, Anthropology and History of Peru. Methodology: first we made the recognition of the skulls and registered their codes adopted according to regions or cultural associations by Curatorship. Then the skulls were photographed following anatomical standards. The information obtained was through observation of high-resolution images. Results and conclusions: cephalic deformations are consistent with the law of Virchow. Pre-columbian Peru summarizes two phylum, “llautu” associated with andean cultures and “cuna” to coastal towns. Llautu is consistent with the early closure of the sagittal suture and consequently the brain as organic matter influences the bregma and the coronal suture stimulating an ossification of a dolichocephalous cranium of annular aspect. “Cuna” is concordant with the early closure of the coronal suture and consequently the brain in growth stimulates suture membranes: sagittal, parietosphenoidal and parietotemporal, leading to brachycephalic skull ossification of a tabular appearance